EVALUASI HASIL BELAJAR SISWA DI SMA AL-ISLAM 1 SURAKARTA - Khairul Huda, Salahudin; Umi Najah; Nabila Farah Dina; Muhammad Dimas Saputra; Anand Azhari Matondang (CV. Kalimasada Group, 2025)
This research aims to elaborate on the evaluation methods used by teachers at SMA Al-Islam 1 Surakarta. Assessing students' learning outcomes is crucial for understanding their proficiency in comprehending and applying concepts of Islamic teachings. Employing a qualitative approach involving interviews, observations, documentation, and literature review, this study delves into the evaluation practices at SMA Al-Islam 1 Surakarta. Data collection and analysis reveal that teachers employ both test-based and non-test-based evaluation methods, including daily quizzes, written assignments, and behavioral observations. They ensure objectivity through clear answer keys and assessment rubrics, accommodating diverse learning styles. Evaluations are conducted gradually and strategically, integrating quantitative and qualitative results aligned with the Merdeka curriculum. Teachers address challenges of time and resources by planning evaluations systematically and adapting measurement tools to students' needs for effective and accurate assessments.